Rethinking strategic alignment: the great powers' wedging and Turkey's balancing strategies. (27th May 2022) - Barlas, Dilek; Yılmaz, Suhnaz
ABSTRACT : The key puzzle that this article explores is how the Great Powers' wedging strategies and Turkey's efforts to balance these powers defined complex strategic alignment dynamics during the 1930s and World War II. We posit that in the 1930s, as Turkey strove to balance the European great powers, these powers resorted to wedging strategies to sway Turkey away from any other sphere of influence. During World War II, increasing US engagement in the region compelled Ankara to utilize a 'dual balancing strategy' to preserve its neutrality, by balancing between the Axis and the Allies and between the British and the Americans. Concomitantly, both Allies and Axis powers utilized predominantly reward-wedging strategies to keep Turkey away from the opposing bloc. We assert that in rethinking strategic alignment more emphasis should be placed on the interactive nature of wedging process and the role and motives of agency.